The Influence of Content Marketing, Digital Human Resource Competence, and Social Media Communication Response on MSME Consumer Trust through Customer Engagement as a Mediating Variable - Nugrahini Susantinah Wisnujati; Abu Muna Almaududi Ausat; Syamsuri Syamsuri; Susatyo Adhi Pramono; Hizbul Khootimah Azzaakiyyah; Muhammad Aqib Shafiq (Institute of Multidisciplinary Research and Community Service, 2026)
This study aims to analyze the influence of content marketing, digital human resource (HR) competence, and social media communication response on consumer trust in micro, small, and medium enterprises (MSMEs), with customer engagement acting as a mediating variable. The research is motivated by the increasing importance of digital marketing in strengthening consumer trust, particularly among micro, small, and medium enterprises (MSMEs) that often face limitations in technological capability and human resources. This study employed a quantitative explanatory approach involving 100 micro, small, and medium enterprises (MSMEs) in Malang City that actively utilize social media as a marketing platform. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings indicate that content marketing, digital human resource (HR) competence, and communication responsiveness on social media positively and significantly influence consumer trust. Customer engagement also has a direct and significant effect on consumer trust. However, the mediation analysis reveals that customer engagement does not significantly mediate the relationship between content marketing, digital human resource (HR) competence, communication response, and consumer trust. These results suggest that consumer trust in micro, small, and medium enterprises (MSMEs) is primarily shaped directly by content quality, digital capabilities, and professional communication rather than by engagement mechanisms. The study contributes theoretically by strengthening the application of the Theory of Planned Behavior and Customer Engagement Theory in the context of digital marketing for micro, small, and medium enterprises (MSMEs). In practical terms, the findings provide strategic insights for micro, small, and medium enterprises (MSMEs) to sustainably and competitively improve consumer trust through consistent content, enhanced digital competence, and responsive communication in the digital era. Keywords: content marketing, digital HR competence, communication response, consumer trust, MSMEs, customer engagement.